2015
DOI: 10.1016/j.ijsu.2015.04.079
|View full text |Cite
|
Sign up to set email alerts
|

ASA class is a reliable independent predictor of medical complications and mortality following surgery

Abstract: ASA PS has strong, independent associations with post-operative medical complications and mortality across procedures. This capability, along with its simplicity, makes it a valuable prognostic metric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
276
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(333 citation statements)
references
References 22 publications
26
276
0
7
Order By: Relevance
“…Nicholas firstly proposed that ASA score has a strong ability to predict surgical complications and perioperative mortality (21), and then Agostini showed that the risk of PCs increased by 3.9 times in patients with ASA score ≥3 after lung resection (4), our study also shows that ASA score was associated with MPCs in NSCLC patients after VATS lobectomy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Nicholas firstly proposed that ASA score has a strong ability to predict surgical complications and perioperative mortality (21), and then Agostini showed that the risk of PCs increased by 3.9 times in patients with ASA score ≥3 after lung resection (4), our study also shows that ASA score was associated with MPCs in NSCLC patients after VATS lobectomy.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies on the prognosis of lung cancer are often focused on tumor size, lymph node metastasis, distant metastasis, chemotherapy sensitivity and other clinical pathology features (20). In recent years, more and more research began to focus on the patient's own factors, such as: the patient's physical condition, immune status, depression (21). However, the impact of perioperative complications on the outcome of the lung cancer patients has been seldom studied (11), this study is the first to determine the association between MPCs and long-term outcomes among patients undergoing VATS lobectomy for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the American Society of Anesthesiologists Physical Status (ASA-PS) classification for the patients was also obtained 8) . …”
Section: Investigationmentioning
confidence: 99%
“…The ASA grade takes into account disease severity and is a reliable metric for the measurement of postoperative mortality and complications19. The RCRI is used to estimate a patient's risk of perioperative cardiac complications, including cardiac death, non‐fatal myocardial infarction and non‐fatal cardiac arrest20.…”
Section: Methodsmentioning
confidence: 99%